Cognitive Cultural Competence and Organizational Identification in Deposit Money Banks in Rivers and Bayelsa States in Nigeria - NWAIROEGBU-AGBAM; Moses Chinedu (IJRDO - Journal of Business Management, 2020)
This study examined the relationship between cognitive cultural competency and organizational identification in Deposit Money Banks in Rivers and Bayelsa States in Nigeria. The study adopted a cross-sectional survey design. The population of the study was 300 managers of 18 Deposit Money Banks Regional Offices in Port Harcourt. A sample size of 169 was determined using Krejcie and Morgan (1970) table for sample size determination. The reliability of the instrument was achieved using Cronbach Alpha Coefficient with all the items attaining coefficients surpassing the threshold of 0.70 Spearman’s rank correlation was used for hypothesis testing. The study findings revealed that there is a significant relationship between cognitive cultural competency and organizational identification and as such, influence outcomes such as oneness, loyalty and membership. The study recommends that managers should develop their cognitive competence with a view to stimulate employees to work towards the achievement of the organizational objectives, the objectives and the organizational values should be more than a sign on the wall.